A Reversible and Highly Selective Inhibitor of the Proteasomal Ubiquitin Receptor Rpn13 Is Toxic To Multiple Myeloma Cells - Trader, Darci J. (J Am Chem Soc, 2015)
The proteasome is a multi-subunit complex responsible for most non-lysosomal turnover of proteins in eukaryotic cells. Proteasome inhibitors are of great interest clinically, particularly for the treatment of multiple myeloma (MM). Unfortunately, resistance arises almost inevitably to these active site-targeted drugs. One strategy to overcome this resistance is to inhibit other steps in the protein turnover cascade mediated by the proteasome. Previously, Anchoori et al. identified Rpn13 as the target of an electrophilic compound (RA-190) that was selectively toxic to MM cells (Cancer Cell 24, 791–805 (2013)), suggesting that this sub-unit of the proteasome is also a viable cancer drug target. Here we describe the discovery of the first highly selective, reversible Rpn13 ligands and show that they are also selectively toxic to MM cells. These data strongly support the hypothesis that Rpn13 is a viable target for the development of drugs to treat MM and other cancers.